Medicinal plants indications from herbal healers for wound treatment - Maria Willianne Alves do Nascimento; Regina Célia Sales Santos Veríssimo; Maria Lysete de Assis Bastos; Thaís Honório Lins Bernardo (Universidade Federal de Goias, 2016)
The objective was to identify medicinal plants indicated by commercial herbal healers for wound treatment, in street markets. A descriptive study conducted in a capital city in the northeast of Brazil, through interviews. The results indicate that plant commerce by healers of both genders, aged between 37 to 52 years, from those 69.3% learned about their function with family members. Forty-eight plant species were cited for wound treatment, between those, all participants cited Barbatimão and Mastic. From the plants Sambacaitá, Open Nettle, Yellow Uchi, Corona, Xiquexique, Senna and Pindaíba no properties to prove their indication was found for wound treatment. The stem bark was the most indicated part (96.15%), 81.03% of participants informed that plants should be kept dry for conservation. Studies to clarify the biological activities and collateral effects of medicinal plants are needed, beyond training for healers about indications, prepare, storage/conservation, and expiration date.